Tingkat Bahaya Kebakaran dan Kerapatan Lahan Gambut di Hutan Lindung Gambut Sungai Buluh Jambi: Fire Danger Level and Peatland Density in The Jambi Buluh River Peat Protected Forest - Istomo, Istomo; Putra, Erianto Indra; Berliyana, Cincy (HUTAN TROPIKA, 2025)
Forest and peatland fires are serious environmental issues in Indonesia, including in Jambi Province. This study aims to identify fire hazard levels based on peatland vegetation density using the Normalized Difference Vegetation Index (NDVI) method in the Sungai Buluh Peat Protected Forest (HLG), Jambi. NDVI data were obtained from satellite imagery and analyzed to assess vegetation density, which was then correlated with fire hazard levels. A total of 12 plots measuring 50 m x 50 m each were established. Based on NDVI analysis, density classes were divided into class 1 (0.0573-0.307), class 2 (0.307-0.398), and class 3 (0.398-0.584). The study area was predominantly occupied by rengas laut stands. The results indicated that areas with low NDVI values have a higher fire risk compared to areas with high NDVI values. The dominant stand type was rengas laut. NDVI and humidity showed the highest correlation (0.780).